Практикум по экологии: учебное пособие - Ларионова Е. В. Екатерина Владимировна; Вторушина А. Н. Анна Николаевна; Гусельников М. Э. Михаил Эдуардович; Назаренко О. Б. Ольга Брониславовна (Томск, Изд-во ТПУ, 2011)
Заглавие с титульного экрана